Nanomaterials as a catalyst for biofuel production - Liu, Zhongchuang; Islam, Md. Azharul; Rizwan, Muhammad (WALTER DE GRUYTER GMBH, 2025)
In the quest for sustainable energy, biofuels emerge as a viable alternative to fossil fuels. Edited by Vivek Dave and Arindam Kuila, Nanomaterials as a Catalyst for Biofuel Production explores the transformative role of nanomaterials in biofuel production, covering biodiesel, bioethanol, biogas, and biohydrogen. The book also delves into environmental bioremediation and techno-economic analysis, offering a comprehensive blend of fundamental concepts and practical applications. It serves as a crucial reference for advancing efficient, sustainable biofuel technologies to drive the global shift toward green energy. This article outlines the main content of each chapter in the book and summarizes the key points of the book. Furthermore, it points out the advantages and disadvantages of this book. The book review is helpful in guiding readers to read the key content of the book and grasp the latest research directions of biofuel production, which is meaningful.
Keywords: green chemical chemistry; catalyst; sustainability; bioenergy; Engineering